Interest Clause in the Constitutional Lawsuit in Accordance to the Constitutional Court in Jordan - Al-Shabatat, Mohammed Ali; Al-Kasasbeh, Hisham Hamed Salman (European Scientific Journal, ESJ, 2017)
This study aimed to shed light on one of the most important conditions of interest for lifting the constitutional validity of the case before the constitutional court. Through this statement, the concept of interest as a condition for accepting the constitutional lawsuit, as well as the right protected by the constitutional lawsuit is a right guaranteed by the Constitution. Also, the assault which is basically the work of public authorities may take the form of the Act of Parliament, regulations, or an administrative decision issued by the executive authority. This is together with various characteristics that must be met for the interest clause in the constitutional case. The existence of a link between the interest on the constitutional lawsuit; the interests of the substantive suit; legal, personal and direct interest; the interest of the list established by law; and the interest clause in the lawsuit should be made available throughout the stages of the proceedings. This should be made available when required at the time filed. Also, it should continue to exist based on the verdict. This occurs especially if the interest is still available before the court reaches a verdict for any reason consequent upon expiration of the constitutional case.